Abnormal Anatomical Position and Number of Renal Artery at the Renal Hilum - Sinha, Rajiv Ranjan; Binod Kumar; Ashish, Kumar; Akhtar, Md Jawed; Kumar, Aman; Kumar, Sanjeev; Kumar, Vinod (Journal of Indian Academy of Forensic Medicine, 2015)
The development of the renal vessels, account for the fact of the complicate development of the kidney. The present study was under taken in 20 embalmed cadavers. Careful dissection of renal hilar structures was carried out to observe antero-posterior relationship of structures at the hilum of the kidney. In majority, the arrangement was according to the normal textbook description i.e. renal vein, renal artery and renal pelvis arranged antero-posteriorly. In 5% of cases renal artery was seen in front of renal vein and renal pelvis at the hilum. In present study, two cadavers showed one Lt Accessory renal arteries and bilateral abnormal arrangement of hilar structure at hilum.The knowledge of variations of the renal vessels forms and its abnormal arrangement at hilum are essential guideline for Urosurgeon during the kidney transplantation and segmental resection for hilar mass. It is also helpful for physician in diagnosis of different renal disease caused by compression of ureter by renal vessels; the wrong diagnosis of which may create problem in the court of law when a case of negligence is brought against a treating physician.
Keywords: Accessory renal artery; Segmental resection; renal hilum; Variations; court of law; Negligence